EFEKTIVITAS PERATURAN DAERAH NOMOR 5 TAHUN 2017 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DI KOTA DUMAI TAHUN 2020-2021 - Raisa Hakim Nasution; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The protection and management of the environment is aimed at preserving the function of the environment by maintaining its carrying capacity and capacity in order to support the implementation of sustainable development. In order to support environmental conservation, Dumai City Regional Regulation No. 5 of 2017 concerning Environmental Protection and Management with the aim of protecting the Dumai City area from pollution and/or environmental damage, especially in the waters of Dumai City. There are several cases of pollution carried out by several companies operating around the port so this needs to be analyzed further regarding the effectiveness of the policies that have been set and the role of the relevant agencies in it. The method used in this research is descriptive method with qualitative research type. The types of data in this research are primary data and secondary data. The data analysis technique used is descriptive qualitative data analysis. The results of this study are the effectiveness of the Dumai City Regional Regulation Number 5 of 2017 concerning Environmental Protection and Management as well as the efforts made by the Regional Government in implementing environmental protection and management in Dumai City. There are 4 (four) indicators used to measure the effectiveness of the policy, which in its implementation can be said to be effective. In this case, the local government has also made several efforts in overcoming cases of environmental pollution that occurred in the port area of Dumai City, including conducting outreach activities, checking standard operating procedures (SOP) for environmental supervision, inspecting company infrastructure, and examining the management of Hazardous and Toxic Waste (LB3). Keywords: Effectiveness, Accuracy of Program Targets, Program Socialization, Program Objectives, Program Monitoring